Multi selection control algorithm in examination invigilation management system (ExIMS) for exchanging invigilation duties among invigilators at UiTM Pulau Pinang branch / Jamal Othman …[et al.] - Othman, Jamal; Syed Abdullah, Sharifah Sarimah; Samsudin, Norshuhada; Wan Mohd Rosly, Wan Nur Shaziayani (UiTM Cawangan Perlis, 2021)
Invigilation of the examination is one of the important roles and tasks of lecturers appointed as invigilators or proctors. Based on the past semi-annually reports of examination post-mortems meeting, less than 10% of the invigilators were unhappy with the examination duties that have been assigned or appointed to them. The examination committee members who are responsible in the process of assigning the invigilation duties to each invigilator had given a lot of effort and spent a few weeks to ensure that everybody is happy with the invigilation duties assigned to them. Nevertheless, despite the excellent planning of invigilation duties assignment, it cannot make everybody satisfied. Thus, a web-based application system named Examination Invigilation Management Systems (ExIMS) has been developed using the System Development Life Cycle (SDLC) waterfall model methodology to meet the need of invigilation duties exchanged among invigilators or applicants. This system has been developed to control and cross check the request of invigilation duties exchanged using the algorithm named multi selection control. The algorithm could avoid any conflicts or anomalies that could happen after the exchange of duty has been made. The process of duty exchange is examined and verified automatically by the system. The system provides a platform for users or invigilators to give their views or opinions on the invigilation duties and system features or performance through the online survey. The survey uses the TAM method concentrating on the perceived-ease-of-use (PEOU) component. Based on the survey, 95% respondents reported that they were satisfied with the platform for duty exchange among invigilators. The users can easily and flexibly select the new duties, which will be automatically and mutually swapped among invigilators. ExIMS has solved the problem of unsatisfaction of invigilation duties and increased the happiness index among invigilators during the examination period.